Engineering of LOV-domains for their use as protein tags - Kaya, Saniye G; Hovan, Andrej; Fraaije, Marco W (Archives of biochemistry and biophysics, 2025)
Light-Oxygen-Voltage (LOV) domains are the protein-based light switches used in nature to trigger and regulate various processes. They allow light signals to be converted into metabolic signaling cascades. Various LOV-domain proteins have been characterized in the last few decades and have been used to develop light-sensitive tools in cell biology research. LOV-based applications exploit the light-driven regulation of effector elements to activate signaling pathways, activate genes, or locate proteins within cells. A relatively new application of an engineered small LOV-domain protein called miniSOG (mini singlet oxygen generator) is based on the light-induced formation of reactive oxygen species (ROS). The first miniSOG was engineered from a LOV domain from Arabidopsis thaliana. This engineered 14 kDa light-responsive flavin-containing protein can be exploited as protein tag for the light-triggered localized production of ROS. Such tunable ROS production by miniSOG or similarly redesigned LOV-domains can be of use in studies focused on subcellular phenomena but may also allow new light-fueled catalytic processes. This review provides an overview of the discovery of LOV domains and their development into tools for cell biology. It also highlights recent advancements in engineering LOV domains for various biotechnological applications and cell biology studies.
Keywords: LOV domain; Reactive oxygen species; Protein engineering; Protein Engineering; Light; miniSOG; reaktivní formy kyslíku; proteinové inženýrství; světlo; Arabidopsis Proteins; Protein localization; Optogenetics; proteiny huseníčku; Protein Domains; Reactive Oxygen Species; Arabidopsis; Humans; Light-responsive proteins; proteinové domény; lidé